Guam-Virgin Islands Elective Governors : hearings before the United States Senate Committee on Interior and Insular Affairs, Subcommittee on Territories and Insular Affairs, Ninetieth Congress, first session, on Feb. 20, Apr. 26, 1967. (U.S. Congressional Hearings., 1967)
Considers (90) S. 449, (90) S. 450.